Characteristics of Anemia in the Elderly: Hospital-Based Study in West Java - Agnes Rengga Indrati; Yehezkiel Yonathan; Hendro Hendro; Lazuardi Dwipa; Cissy Kartasasmita (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Geriatric anemia can cause many problems and is a major health condition worldwide and in Indonesia. It is important to know the characteristics and prevalence of anemia among geriatrics in Indonesia, especially in West Java. By using simple hematology parameters to detect anemia in geriatrics, and then giving adequate treatment, morbidity, and mortality due to anemia may decrease in geriatrics. This study aimed to identify the type of anemia, etiology, age, gender, and prevalence of elderly patients with anemia in West Java. This was a cross-sectional study. Patients above 59 years old attending the geriatric clinic in Hasan Sadikin General Hospital and the geriatric community was included in this study to be evaluated for anemia, the characteristics of anemia (normocytic, microcytic, and macrocytic) based on MCV and MCHC, age group (<=65 and > 65 year old), and gender. Among 247 elderly patients, anemia was found in 33 patients (13.64%) and mostly found in females. Mostly represented as normochromic normocytic anemia (78.8%) and microcytic hypochromic anemia (21.2%), respectively. Individuals older than 65 years old were mostly presented with microcytic hypochromic anemia (66.7%). Meanwhile, normocytic normochromic anemia was more commonly found in individuals below 65 years old (12.1%). Anemia was commonly found in people older than 65 years old. The most common type of anemia in geriatrics in West Java was normocytic normochromic. Females experience anemia more than males.